Antioxidants in Arrhythmia Treatment-Still a Controversy? A Review of Selected Clinical and Laboratory Research - Jakub Szyller; Dariusz Jagielski; Iwona Bil-Lula (MDPI AG, 2022)
Antioxidants are substances that can prevent damage to cells caused by free radicals. Production of reactive oxygen species and the presence of oxidative stress play an important role in cardiac arrhythmias. Currently used antiarrhythmic drugs have many side effects. The research on animals and humans using antioxidants (such as vitamins C and E, resveratrol and synthetic substances) yields many interesting but inconclusive results. Natural antioxidants, such as vitamins C and E, can reduce the recurrence of atrial fibrillation (AF) after successful electrical cardioversion and protect against AF after cardiac surgery, but do not affect the incidence of atrial arrhythmias in critically ill patients with trauma. Vitamins C and E may also effectively treat ventricular tachycardia, ventricular fibrillation and long QT-related arrhythmias. Another natural antioxidant-resveratrol-may effectively treat AF and ventricular arrhythmias caused by ischaemia-reperfusion injury. It reduces the mortality associated with life-threatening ventricular arrhythmias and can be used to prevent myocardial remodelling. Statins also show antioxidant activity. Their action is related to the reduction of oxidative stress and anti-inflammatory effect. Therefore, statins can reduce the post-operative risk of AF and may be useful in lowering its recurrence rate after successful cardioversion. Promising results also apply to polyphenols, nitric oxide synthase inhibitors and MitoTEMPO. Although few clinical trials have been conducted, the use of antioxidants in treating arrhythmias is an interesting prospect.